Homem e internet móvel : mundos criados entre dedos e cliques - Rangel, Paula Maria Valdetaro (2014)
This dissertation proposes to think about how, in contemporary times, the subject provided with devices connected to the mobile internet produces the world and produces himself concomitantly in this process. The mobile internet for its almost omnipresence in our lives and spaces, draws attention and makes important vector in the constitution of the subject and the world today. What is visible, sensitive and thought-provoking in this research is that to be (all the time and everywhere) connected – online -seems to be one veredict: being networked is the contemporary presence. The bodies connected to each other, share their lives, their habits, what they eat, what they wear, where they go, who they are and this share creates and recreate the selves. Therefore, in this dissertation was made a theoretical research, which has three main parts. At first, we discuss about the composition of contemporary subjectivity and the construction of the subject in actuality, being Rolnik and Guattari, Kastrup and Favre the main authors intercessors. We emphasize presence of the forces and shapes ways, constantly modified and recreated as constituents of reality. In the second chapter, we discuss the relationship between man and technique from the considerations of Liliana Escóssia, dialoguing with authors such as Lévy, Negri and Latour and it is stated the defense to think and analyze the technical man-relationship from a ontongenética conception, which gives emphasis to this relationship processuality. In the third and final chapter, the discussion revolves around the mobile internet and its aftermath in the contemporary: its use and transformation of individuals, the environment and the technology itself. Lucia Santaella and André Lemos appear as the main debaters. changing the use of public space is the main feature discussed by these authors, encompassing issues as urban mobility, interstitial spaces and locative media. Bruno Latour is the central theoretical intercessor in discussions of Lemos and Santaella, specifically for his actor-network theory. stands out in this chapter, the need for analysis and observation of the engagement with the mobile internet. We conclude that mobile internet man-vector relationship is striking in contemporary subjectivity and that this relationship is marked by speed, for transformations in modes of being, of relating to space, modes of study and to relate to media communication. Points to the co-emergence of subjects and mobile internet itself bias, which can not only try to qualify as a good or bad use, but be aware of the traces and the agency of humans and nonhumans in the construction of contemporary subjectivity.